A review study of numerical modeling of the impulse wave caused by the sliding of masses into still waters and parameters affecting it - Fateme Maleki; Jalal Bazargan; Zahra Maleki (مهندسی و مدیریت ساخت)
The phenomenon of impulse waves caused by soil mass sliding into water is one of the important issues in geotechnical and hydrodynamic engineering, which can have destructive consequences on the environment and coastal structures. These waves are widely observed in nature and engineering environments and have multiple effects on the surrounding structures and environments. These waves are caused by the sudden entry of the soil mass into the water, and their investigation is of great importance, especially using numerical methods. In this study, a comprehensive review of the numerical researches conducted in the field of impulse waves caused by landslides is presented. This article examines different numerical models, key parameters affecting wave generation and validation of numerical results compared to experimental data. Also, the challenges in the numerical simulation of this phenomenon and the proposed solutions to improve the accuracy of the modeling have been investigated. The results of this study can help to improve the understanding of this phenomenon and develop new simulation methods.